الظروف الأسرية للتلاميذ ذوي السلوك المضطرب - بلعظم, نادية (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى استقصاء الظروف الأسرية للتلاميذ ذوي السلوك المضطرب، على عينة من تلاميذ السنة الثانية متوسط بلغ عددهم (11) تلميذ وتلميذة، وتمثل السلوك المضطرب الذي أظهروه فيما يلي: العدوانية وإثارة المشكلات مع الزملاء والأساتذة، قلة احترام وتشويش داخل القسم، لباس ومظهر غير مناسب، تصرفات لا أخلاقية، وتعدد العلاقات العاطفية. وبالرجوع إلى ملفاتهم المدرسية، والاستقصاء عن أحوالهم وظروفهم الأسرية ممن يعرفونهم تبيّن أنهم يعانون إما من: طلاق الوالدين، والد مسجون أو يعمل بعيدا عن المنزل، فقر، أو في جو مشحون مليء بالصراعات والمشاكل العائلية، أو تسلط وعدائية الآباء. Abstract: This study aims to investigate the family conditions of students with disordered behavior, on a sample of 11 students from the second year, the behavioral disorders were as follows: aggressiveness and causing problems with colleagues and professors, disrespect and inconvenience within the department, inappropriate dress and appearance, unethical behavior, and multiple emotional relationships. After checking the conditions of their families, it was found that they suffer from either: the divorce of the parents, the imprisonment of the father, his work away from home, poverty, Or in an atmosphere of disagreements and family problems or authoritarian and aggressive parents.
مقال
Keywords: الظروف الأسرية ; السلوك المضطرب; Family conditions; Behavior disorder